2001
DOI: 10.1002/ajmg.1194
|View full text |Cite
|
Sign up to set email alerts
|

No association of two missense variations of the benzodiazepine receptor (peripheral) gene and mood disorders in a Japanese sample

Abstract: The benzodiazepine receptor (peripheral) (BZRP) plays an important role in the steroid syntheses of the adrenal glands and brain, which is possibly involved in the pathophysiology of mood disorders. We evaluated an association study between two missense variations of the BZRP gene and mood disorders in a Japanese sample. However, no statistically significant associations with either bipolar disorders or depressive disorders were observed in the allele frequencies, genotype counts, or haplotype distributions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…1B). The same variations were reported in the PBR gene isolated from other human tumoral cell lines (Hardwick et al, 1999) and, with high frequency, in genomic DNA of normal cells (Kurumaji et al, 2001).…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…1B). The same variations were reported in the PBR gene isolated from other human tumoral cell lines (Hardwick et al, 1999) and, with high frequency, in genomic DNA of normal cells (Kurumaji et al, 2001).…”
Section: Methodssupporting
confidence: 77%
“…Here, we report that Jurkat cells expressed PBR with unusual affinity constants for PBR ligands. Moreover, we demonstrated that the Jurkat PBR gene contains two point mutations reported previously in other human tumoral cell lines (Hardwick et al, 1999) and in normal cells (Kurumaji et al, 2001). …”
supporting
confidence: 76%
See 1 more Smart Citation
“…It should be noted that a study in a Japanese sample (n. cases = 94; n. controls = 359) found no association of rs6971 with BD (Kurumaji et al, 2001). However, whilst the minor allele frequency is 30% in Europeans, it is only 4% in the Japanese population.…”
Section: Discussionmentioning
confidence: 86%
“…Genotypic and allelic analyses of the 485G > A revealed significant differences between patients with panic disorder and the comparison subjects [171]. However, no association of two missense variations of the PBR gene and mood disorders was found in a Japanese sample [172].…”
Section: Gaba and Depression In Humansmentioning
confidence: 97%